Mobile X-band Direction Finder - Ivanchenko, I.; Ivanchenko, D.; Korol, A.; Popenko, N.; Radionov, S. (ХНУРЭ, 2008)
A compact X-band direction finder is presented in this paper. Algorithm of the system operation using the “null-amplitude” technique is described in detail. Based on the results of model experiments the resolving capacity of the direction finder prototype are determined.
Keywords: compact X-band direction; “null-amplitude” technique